WiFi-Based Location Tracking: A Still Open Door on Laptops - Mariana Cunha; Ricardo Mendes; Yves-Alexandre de Montjoye; Joao P. Vilela (IEEE Open Journal of the Computer Society)
Location privacy is a major concern in the current digital society, due to the sensitive information that can be inferred from location data. This has led smartphones’ Operating Systems (OSs) to strongly tighten access to location information in the last few years. The same tightening has, however, not yet happened when it comes to our second most carried around device: the laptop. In this work, we demonstrate the privacy risks resulting from the fact that major laptop OSs still expose WiFi data to installed software, thus enabling to infer location information from WiFi Access Points (APs). Using data collected in a real-world experiment, we show that laptops are often carried along with smartphones and that a large fraction of our mobility profile can be inferred from WiFi APs accessed on laptops, thus concluding on the need to protect the access to WiFi data on laptops.